SP0042 Future challenges for health professionals: Communication across health care levels. (23rd January 2014) - Prodinger, B.
Abstract : Delays in seeking primary care lead to late referrals to secondary care in people with rheumatoid arthritis, which in turn may impact on treatment outcomes. To ensure timely, comprehensive, and continuous care for people with rheumatoid arthritis, the role of health professionals in primary and secondary care is complex goes beyond the treatment of disease-related symptoms and entails supporting people with rheumatoid arthritis in managing their daily lives and enabling them to participate in work and social life. Such provision of care may challenge or might be challenged within systems that are predominantly structured around the treatment of disease-related symptoms. Communication and collaboration of health professionals within and across care levels becomes then even more important. Some of the challenges in communicating across care levels include existing processes and structures that regulate the interface between primary and secondary care and services that can be made accountable at each care level. For instance information exchange across health professionals and care levels might be something that cannot be made accountable within certain institutional processes and structures. In this lecture I draw upon an ongoing comparative institutional ethnographical study about routine treatment processes in the provision of care to patients with rheumatoid arthritis in Austria, Sweden, and the UK. The insights gained from this study exemplify how processes and structures, which regulate the interface of primary and secondary care and the scope of practices at each level, differ in the three countries and open up varying possibilities and challenges for communication across care levels. This lecture concludes with some reflections based on this comparative study and opens up for discussion how communication across care levels can be facilitated and fostered while remaining sensitive to the varying possibilities and challenges that health professionals in different countries face in their daily practices. Disclosure of Interest: None Declared